“There are days when you feel alone”: Exploring EFL teachers’ perception of interaction in online classes - Benjamin Carcamo Morales; Claudio Hernandez (Colombian Applied Linguistics Journal)
COVID-19 has made many educational institutions shift to virtual learning environments. One of the main issues in doing so has been the types of interactions that are generated online. Considering the importance of interaction in second language acquisition, it is relevant to learn how EFL teachers are facing the challenge of fostering interaction in the virtual classrooms. The purpose of this study was twofold: First, we explored EFL Chilean university teachers’ use of digital tools in their virtual classrooms to promote interaction. Secondly, we analyzed the obstacles they have faced promoting interaction. Our findings show that although EFL teachers have not had difficulties implementing different digital tools and platforms, interactions among learners are lacking.  Students keeping microphones and cameras off has become a variable that reduces the possibility of knowing whether students are paying attention, monitoring their work, and setting up groupwork. An alarming finding was that this issue may increase EFL teachers’ feeling of isolation in the virtual classroom. We expect our findings help institutions focus their efforts on supporting EFL teachers teaching online as well as propel future studies on effective teaching practices to promote interaction among learners in virtual classrooms.